2019
DOI: 10.1016/j.heliyon.2019.e02950
|View full text |Cite
|
Sign up to set email alerts
|

Application and optimization of ultrasound-assisted deep eutectic solvent for the extraction of new skin-lightening cosmetic materials from Ixora javanica flower

Abstract: The high demand for cosmetics has had a great impact on the development of innovative products in the cosmetic industry. The availability of raw materials has become a common problem in the cosmetic industry. Materials from nature can act as alternative sources, such as Ixora javanica. Several studies have shown the potential of I. javanica as an antioxidant and skin lightening agent. The objectives of the present study were to develop and optimize a green ultrasound-assisted deep eutectic solvent extraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…To the best of our knowledge, no published studies regarding AChE and BChE inhibition capacity of NADES itself or NADES extracts were found in the literature. Only one study was found about the Tyr inhibition capacity of Ixora javanica flower extracts obtained with various DES [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no published studies regarding AChE and BChE inhibition capacity of NADES itself or NADES extracts were found in the literature. Only one study was found about the Tyr inhibition capacity of Ixora javanica flower extracts obtained with various DES [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanins were extracted using UADESE in accordance with a previously described method, with some modifications [ 22 ]. The lyophilized raspberry powders were mixed with the prepared DESs under different solid-to-liquid ratios and carried out using RY-TQ-C ultrasound equipment (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The selection of HBA and HBD should be adjusted to the target compound according to the ‘like dissolve like’ principle. Our previous study reported that a combination of choline chloride as an HBA and propylene glycol as an HBD offers the most effective flavonoid extraction from I. javanica flowers out of 11 other types of DES [ 17 ]. In the extraction process, the viscosity of DES is a common problem [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total levels of flavonoids in the extracts were determined using the method applied in the previous study with very slight modifications [ 17 ]. About 1.0 ml of each extract's filtrates was mixed with 1.5 ml of 0.33% AlCl 3 and 1.5 ml of 10% acetic acid solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation